Emotional intelligence and personality predict the leadership practices of future muslim leaders - Wan Husin, Wan Nurul Izza; Santos, Angeli; Ramos, Hazel Melanie; Dzulkifli, Mariam Adawiah (University Malaya, 2014)
Despite a growing number of studies focused on the emotional intelligence and leadership of professional working groups, the construct of emotional intelligence has received little attention in literature related to undergraduate leadership development. This study investigates the influence of personality traits and emotional intelligence on the leadership of future Muslim leaders. The main objective of this study is to assess the incremental validity of emotional intelligence over the personality factors in predicting leadership practices. Data were collected from 710 Muslim undergraduate students who constitute future leaders. Results from regression analysis, particularly the relative weight analysis, reveal that emotional intelligence demonstrated significant incremental variance with leadership practices beyond the personality traits. The implications of the findings for research and practice are discussed.